Implementasi Metode Qirā’ah dan Imlā’ dalam Meningkatkan Keterampilan Membaca dan Menulis Bahasa Arab Siswa Kelas V MI Salafiyah Kasim Ploso Selopuro Blitar - Salimna Birohmatin; Nurul Huda; Agung Setiyawan; Naela Alfa Ruhama (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
This research is motivated by the low reading and writing skills of students in Arabic language learning. The lack of engaging methods and creative media causes students to lose interest, resulting in poor comprehension of the material. This study aims to examine the implementation of the qirā'ah and imlā' methods to improve Arabic reading and writing skills among fifth-grade students at MI Salafiyah Kasim. The methods used are qirā'ah jahriyah (loud reading) and imlā' manqūl (copied dictation). This is a qualitative descriptive field research conducted at MI Salafiyah Kasim using purposive sampling for data collection. Data analysis includes data reduction, data presentation, and conclusion drawing.The results show that in the qirā'ah jahriyah method, the teacher reads aloud and students imitate, followed by selected students reading aloud in front of the class. In the imlā' manqūl method, the teacher writes vocabulary on the board, students copy it into their notebooks, then read it aloud again.Several challenges were found in the implementation process, including difficulty in managing students during lessons, lack of attention from teachers and parents at home, peer influence from more advanced students, and students’ low self-confidence in learning Arabic.